Overexpression of the Mg-chelatase H subunit in guard cells confers drought tolerance via promotion of stomatal closure in Arabidopsis thaliana - Tsuzuki, Tomo; Takahashi, Koji; Tomiyama, Masakazu; Inoue, Shin-ichiro; Kinoshita, Toshinori (Frontiers in Plant Science, 2013)
The Mg-chelatase H subunit (CHLH) has been shown to mediate chlorophyll biosynthesis, as well as plastid-to-nucleus and abscisic acid (ABA)-mediated signaling. A recent study using a novel CHLH mutant, rtl1, indicated that CHLH specifically affects ABA-induced stomatal closure, but also that CHLH did not serve as an ABA receptor in Arabidopsis thaliana. However, the molecular mechanism by which CHLH engages in ABA-mediated signaling in guard cells remains largely unknown. In the present study, we examined CHLH function in guard cells and explored whether CHLH expression might influence stomatal aperture. Incubation of rtl1 guard cell protoplasts with ABA induced expression of the ABA-responsive genes RAB18 and RD29B, as also observed in wild-type (WT) cells, indicating that CHLH did not affect the expression of ABA-responsive genes. Earlier, ABA was reported to inhibit blue light (BL)-mediated stomatal opening, at least in part through dephosphorylating/inhibiting guard cell H+-ATPase (which drives opening). Therefore, we immunohistochemically examined the phosphorylation status of guard cell H+-ATPase. Notably, ABA inhibition of BL-induced phosphorylation of H+-ATPase was impaired in rtl1 cells, suggesting that CHLH influences not only ABA-induced stomatal closure but also inhibition of BL-mediated stomatal opening by ABA. Next, we generated CHLH-GFP-overexpressing plants using CER6 promoter, which induces gene expression in the epidermis including guard cells. CHLH-transgenic plants exhibited a closed stomata phenotype even when brightly illuminated. Moreover, plant growth experiments conducted under water-deficient conditions showed that CHLH transgenic plants were more tolerant of drought than WT plants. In summary, we show that CHLH is involved in the regulation of stomatal aperture in response to ABA, but not in ABA-induced gene expression, and that manipulation of stomatal aperture via overexpression of CHLH in guard cells improves plant drought tolerance.